Penerapan Teknik Tripod Position dan Pursed Lip Breathing terhadap Kenaikan Saturasi Oksigen pada Pasien Sesak di IGD RSUD Limpung - Soimun Soimun; Dwi Retnaningsih (Jurnal Mahasiswa Ilmu Kesehatan, 2025)
Shortness of breath is one of the main problems experienced by patients with respiratory disorders such as chronic obstructive pulmonary disease (COPD), asthma, pulmonary tuberculosis, and lung cancer. This condition can reduce oxygen saturation, which leads to limitations in physical activity, decreased quality of life, and an increased risk of hypoxemia that may become fatal if not immediately addressed. The management of dyspnea is not only carried out through pharmacological therapy but also through non-pharmacological interventions that are simple, safe, and easy to apply by health care providers. One such intervention is the tripod position and pursed-lip breathing technique. The tripod position is a sitting posture in which the patient leans forward with both hands supporting the body on the knees or a table, thereby facilitating maximum chest expansion. Meanwhile, pursed-lip breathing is a breathing technique performed by inhaling through the nose and exhaling slowly through pursed lips, which prolongs the expiratory phase, reduces trapped air, and improves alveolar ventilation. This study aimed to determine the effectiveness of applying these two techniques in increasing oxygen saturation among patients with dyspnea in the Emergency Department of RSUD Limpung. The research design was a case study involving four patients diagnosed with COPD, asthma, pulmonary tuberculosis, and lung cancer. The intervention was carried out by assisting patients to sit in a tripod position and training them in pursed-lip breathing for approximately 10 minutes. Oxygen saturation was measured using a pulse oximeter before and after the intervention. The results showed an increase in oxygen saturation in all patients, from 92–97% to 95–99% after the intervention. In conclusion, tripod position and pursed-lip breathing proved to be effective non-pharmacological therapies that can be recommended in emergency nursing practice to reduce dyspnea and improve oxygenation.